The natural and artificial radionuclides in drinking water samples and consequent population doses - Altikulac, Aydan; Turhan, Seref; Gumus, Hasan (Elsevier BV, 2015)
AbstractConcentration levels of 226Ra, 228Ra, 40K and 137Cs were determined in 52 drinking water samples collected from the different supplies in Samsun province to evaluate annual effective dose due to the ingestion of the drinking water samples. The activity concentrations of 226Ra, 228Ra and 40K natural radionuclides in the drinking water samples varied from <27 to 2431 mBq L−1, <36 to 270 mBq L−1 and <47 to 2880 mBq L−1 respectively. The activity concentrations of the artificial radionuclide 137Cs in the drinking water samples were lower than minimum detectable activity except in one drinking water sample (DW14) with an associated activity concentration of 2576 mBq L−1. Contributions of the consumed water samples to annual effective dose from 226Ra, 228Ra and 40K varied from 1.6 to 33.4 μSv y−1 with a mean of 6.1 μSv y−1, 2.2 to 46.8 μSv y−1 with a mean of 8.6 μSv y−1, 4.7 to 97.5 μSv y−1 with a mean of 17.9 μSv y−1 for infants, children and adults, respectively. The results showed that all values of the annual effective dose of ingestion of these water samples were below the individual dose criterion of 100 μSv y−1 reported by World Health Organization (WHO).
Keywords: 228Ra; K; Cs; TK9001-9401; R895-920; Annual effective dose; Medical physics. Medical radiology. Nuclear medicine; K-40; Cs-137; Natural radioactivity; Nuclear engineering. Atomic power; Drinking water; Ra-226,Ra-228; 6. Clean water; 3. Good health